Mathematics Learning Interest of Elementary School Students in Using Metaphorical Thinking Learning Model - Febriyanti, Ni Komang Sriasih; Putra, Made (Universitas Pendidikan Ganesha, 2020)
The lack of interest in learning mathematics is one of the most important problems to be solved. It is because the implementation of a learning model has not been maximized which can stimulate active students in the learning process so that it will have an impact on students' interest in learning mathematics. This study aimed to examine the use of the Metaphorical Thinking learning model for students' interest in learning mathematics in the fifth grade of elementary school. The design of the study was a quasi-experiment with a post-test only no treatment control design. The population of the study was 182 students. The samples were taken using a random sampling technique with a total sample of 70 students. In this study, the data was obtained from a non-test method, namely by using a questionnaire. Descriptive analysis techniques and t-test were used in this study. Based on t-test analysis, the value of tcount was 2.256 and ttable at a significance level of 5% was 2.000. Therefore, tcount> ttable, it means that H0 was rejected and Ha was accepted. It can be concluded that the Metaphorical Thinking learning model affects the students’ interest in learning mathematics in the fifth grade of elementary school. The results of this study can be used as a guide or reference for teachers in designing the learning process in schools.